PENERAPAN METODE BERCERITA BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MEMBACA MENULIS PERMULAAN BAHASA INGGRIS - Gede Wira Bayu (Universitas Pendidikan Ganesha, 2019)
PENERAPAN METODE BERCERITA BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MEMBACA MENULIS PERMULAAN BAHASA INGGRIS Gede Wira BayuPendidikan Guru Sekolah Dasar, FIP Universitas Pendidikan GaneshaEmail:wira.bayu@undiksha.ac.id Abstract This research is classroom action research which is involved the students in II/C class SD Negeri 3 Banjar Jawa at the second semester of the academic year 2010/2011. This research implemented in three cycles and the focus of the action is in the implementation of telling story method with drawing media and involved the miter teacher directly in collaborative work to improve student’s interest and achievement in learning reading and writing English for beginners.The result of this research showed that the implementation of telling story method with drawing media is success to improve student’s interest and achievement in learning reading and writing English for beginners. Better attention, willingness, and effort of the students showed that the interest of the students is improved, and better achievement in every cycle from cycle 1, 2 and 3 is appropriate with the aims of this research.Students opinion showed that 52% of them is like the implemented of telling story method with drawing media and 70% of them declared that this method can improved their willingness in studying English especially reading and writing. It’s indicating that this method is effective. Based on the research finding, generally recommended that this method need to be implemented in the elementary school to support the improving interest and achievement of the students in learning English. Key words: Telling story method, Drawing media, Interest and Achievement.